IMPLEMENTASI KEBIJAKAN PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB): STUDI DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN NATUNA - Isnawati, Isnawati; Herdiana, Dian; Mujtahid, Iqbal Miftakhul (Jurnal Ilmiah Mandala Education (JIME), 2022)
The Natuna Regency Government obtained a score below the norm for adopting good governance principles. The Government of Natuna Regency's attempts to enhance the quality of public services, one of which is the issue of Building Permits. The purpose of this study is to examine government collaboration related to the issue of Building Permits policy at the Office of Investment and One Stop Services in Natuna Regency. This study used a qualitative technique with a descriptive approach, using both primary and secondary data. The study's findings indicate that the Building Permits policy has been implemented at the Natuna Regency's Office of Investment and One-Stop Services since 2017. According to the study findings, properly implementing the Building Permits policy requires the following components: communication, resources, disposition, and bureaucracy. Recommendation for the research is focusing on maximize the communication and resource to service related to the issue of building permit